Interhemispheric Comparisons of Large Nighttime Magnetic Perturbation Events Relevant to GICs. Issue 8 (19th August 2020) - Engebretson, Mark J.; Kirkevold, Kathryn R.; Steinmetz, Erik S.; Pilipenko, Viacheslav A.; Moldwin, Mark B.; McCuen, Brett A.; Clauer, C. R.; Hartinger, Michael D.; Coyle, Shane; Opgenoorth, Hermann; Schillings, Audrey; Willer, Anna N.; et al.
Abstract: Nearly all studies of impulsive magnetic perturbation events (MPEs) with large magnetic field variability (d B /d t ) that can produce dangerous geomagnetically induced currents (GICs) have used data from the Northern Hemisphere. Here we present details of four large‐amplitude MPE events (|Δ B x | > 900 nT and |d B /d t | > 10 nT/s in at least one component) observed between 2015 and 2018 in conjugate high‐latitude regions (65–80° corrected geomagnetic latitude), using magnetometer data from (1) Pangnirtung and Iqaluit in eastern Arctic Canada and the magnetically conjugate South Pole Station in Antarctica and (2) the Greenland West Coast Chain and two magnetically conjugate chains in Antarctica, AAL‐PIP and BAS LPM. From one to three different isolated MPEs localized in corrected geomagnetic latitude were observed during three premidnight events; many were simultaneous within 3 min in both hemispheres. Their conjugate latitudinal amplitude profiles, however, matched qualitatively at best. During an extended postmidnight interval, which we associate with an interval of omega bands, multiple highly localized MPEs occurred independently in time at each station in both hemispheres. These nighttime MPEs occurred under a wide range of geomagnetic conditions, but common to each was a negative interplanetary magnetic field B z that exhibited at least a modest increase at or near the time of the event. A comparison of perturbation amplitudes to modeled ionospheric conductances in conjugate hemispheres clearly favored a current generator model over a voltage generator model for three of the four events; neither model provided a good fit for the premidnight event that occurred near vernal equinox. Key Points: Conjugate premidnight MPEs were largest in d B x /d t and were often but not always simultaneous to within 3 min over ~100–700 km in latitude Conjugate postmidnight MPEs were associated with omega bands, often largest in d B y /d t, very localized, and independent in time over ~1.5 hr Perturbation amplitudes and maximum derivatives favored a current generator model over a voltage generator model for near‐solstice events